Preventing re-displacement through genuine reintegration in Burundi - Hovil, L (Refugee Studies Centre, University of Oxford, 2012)
Displacement is often part of a cyclical process of conflict and displacement. Preventing displacement, therefore, is not only about preventing new displacement but about ensuring that people do not get re-displaced.